“Joying in War as in a Feast”. The Construction of Imagery in Greek Ceremonial Armor of the 4th Century B. C - Nalimova, Nadezhda A.; Dedyulkin, Anton V. (Actual Problems of Theory and History of Art, 2021)
This paper offers an attempt to interpret the Classical and Hellenistic ceremonial armaments as constructed artistic images. It concentrates on a group of luxurious armor of the 4th–3rd centuries B.C., which represents or imitates anatomical details, both real and fantastic, as well as clothing and jewelry (e.g. the helmets of the so-called Conversano group, the cuirass from Laos). This characteristic suggests the idea of a certain mythological transfiguration of the armor wearer himself. From a formal point of view, such armor is close to sculpture, stylistic, iconographic, and semantic aspects of which can be identified and analyzed. The only distinction from “real” sculpture is that the owner himself is directly involved in the creation of the image. In the majority of cases, it is not known who the owners of these pieces were, because most of the finds have lost their original context. Nevertheless, based on the available data, the authors attempt to draw conclusions about the possible contexts in which the phenomenon of such “costume-like” armor could have arisen.
Keywords: Hellenism; Classical Age; armor; Macedonia; Apulia; Lucania; Thrace; Dionysian characters; floral decoration